An occupational therapy community of practice within pediatric acute care: fostering professional, social and cultural capital in resource challenged settings/Comunidade de prática de terapia ocupacional em cuidado hospitalar pediátrico: promovendo o capital profissional, social e cultural em contextos desafiadores - Galheigo, Sandra Maria; Braga, Claudia Pellegrini; Magalhães, Lilian; Kinsella, Elizabeth Anne (Cadernos Brasileiros de Terapia Ocupacional, 2019)
Introduction: The need to address the way professional knowledge is produced and delivered, has led some occupational therapy scholars to advocate for the creation of communities of practice (CoP) where practitioners may find a generative environment to engage in reflection with others, to collectively share their knowledge, and to develop professional practice knowledge. CoPs may result in the development of social capital by strengthening practitioners’ social connections and advance cultural capital by improving collaborative forms of reflection and knowledge exchange. Objective: This article presents findings from a participatory action research project regarding the creation of a (CoP) with the aim to implement and examine its affordances among pediatric occupational therapists working in acute care in a Brazilian context. Method: This participatory action research involved nine occupational therapists in 10 face-to-face meetings and in virtual interaction through an e-learning software platform. The community of practice group sessions were recorded, transcribed and coded. The hermeneutic and dialectic method was used as the basis for interpreting the results. Results: Five major themes concerning the affordances of the Occupational Therapy CoP in this context were identified: (i) dialogic engagement; (ii) reflective opportunities; (iii) a sense of belonging; (iv) affirming professional identity; (v) cultivating professional practice knowledge. Conclusion: Developing a CoP in occupational therapy may be a fruitful way to cultivate professional, social and cultural capital amongst occupational therapists who work in resource challenged settings.